Statewide Variation in Practices and Charges for Primary Spontaneous Pneumothorax in Maryland, United States: A Retrospective Study - Grace Lassiter; Eric Etchill; Tamir Sholklapper; Charbel Chidiac; Joseph Canner; Daniel Sangkyu Rhee (Journal of Chest Surgery)
Background: The optimal treatment for primary spontaneous pneumothorax (PSP) remains undefined. Furthermore, the overall utilization and costs of various treatment approaches are incompletely understood. We investigated hospital charges and resource utilization by management strategy across the state of Maryland in adult and pediatric patients with PSP. Methods: We queried the Maryland Health Services Cost Review Commission database for patients aged 10–40 years admitted with PSP between 2012 and 2020. Patients managed with a chest tube alone (CT) were compared with recipients of video-assisted thoracoscopic surgery (VATS). Subsequently, we analyzed hospital charges for patients undergoing early VATS (<48 hours post-admission) vs. delayed VATS (≥48 hours). The predicted incremental cost of early vs. delayed VATS was calculated. Results: Overall, 354 admissions were identified, with 211 (59.6%) receiving CT management and 143 (40.4%) undergoing VATS. Patients receiving VATS were more likely to be female (24% vs. 15%, p=0.030) and Black (32% vs. 20%, p=0.035) than CT recipients. The median total hospital charge for CT recipients was $6,493, compared to $20,437 for patients managed surgically (p<0.001). Delayed surgery during the index admission was associated with significantly higher total hospital charges—including operating room, room and board, radiology, and laboratory costs—than early surgery. Applying early VATS to all patients appeared more cost-efficient than delayed VATS (per-patient costs: $18,568 vs. $30,832, p<0.001), although the former had slightly higher recurrence (7.9% vs. 1.5%, p=0.08). Conclusion: Variations in management strategies, particularly surgical decision-making and timing, impact hospital charges and utilization for patients with PSP.